The Cavern-Mystery Transmission A Taoist Ordination Rite of A.D. 711 - Benn, Charles D. (Asian Studies at Hawaii, 1991)
Very little scholarly research has been done on the institutional structure of Taoism in medieval times. With this study of investiture, Benn attempts to fill that void. He describes the mechanism by which the Taoist priesthood ordered and perpetuated itself, as revealed in a rare account of an ordination rite for two T'ang princesses. He examines the lives of the participants, the hierarchy of the clergy, the liturgy, and the significance of the altar and its furnishings, and discusses other works of Chang Wan-fu, who authored this account.